2018
DOI: 10.1080/1540496x.2018.1474737
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Pass-Through in ASEAN Countries: An Application of the SVAR Model

Abstract: Central banks in emerging countries generally question the effect of exchange rate passthrough into price levels in the national economy in order to implement monetary policy effectively. This paper is conducted in response to these macroeconomic concerns. Five founding members of the Association of Southeast Asian Nations (ASEAN), for which all the required data are available, are included in our sample with up-to-date time-series data until 2016. We use a structural vector autoregressive model in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…In comparison, the estimated ERPT to the consumer price in this paper is greater than the estimates found by Ito and Sato (2007) and Anh, Quan, Phuc, Chi and Duc (2018) and less than the estimates reported by Ito and Sato (2008), Prasertnukul, Kim and Kakinaka (2010) and Kohlscheen (2010). The finding that ERPT to the consumer price declines after the adoption of inflation targeting is consistent with the results reported by Aleem and Lahiani (2014) and Dilla, Achsani and Anggraeni (2017) but in contrast with the finding presented by Prasertnukul, Kim and Kakinaka (2010).…”
Section: Resultssupporting
confidence: 78%
“…In comparison, the estimated ERPT to the consumer price in this paper is greater than the estimates found by Ito and Sato (2007) and Anh, Quan, Phuc, Chi and Duc (2018) and less than the estimates reported by Ito and Sato (2008), Prasertnukul, Kim and Kakinaka (2010) and Kohlscheen (2010). The finding that ERPT to the consumer price declines after the adoption of inflation targeting is consistent with the results reported by Aleem and Lahiani (2014) and Dilla, Achsani and Anggraeni (2017) but in contrast with the finding presented by Prasertnukul, Kim and Kakinaka (2010).…”
Section: Resultssupporting
confidence: 78%
“…Based on the mean values, the elasticity is estimated to be 0.1194, suggesting that a 1% depreciation in the Malaysian ringgit would lead to 0.1194% increase in the consumer price index. In comparison, the estimated ERPT to the consumer price in this paper is greater than the estimates found by Sato (2007, 2008) and Anh, Quan, Phuc, Chi and Duc (2018) but less than the estimates made by Ahmad (2009) and Kassi, Sun, Ding, Rathnayake and Assamoi 2019A 1 percentage point increase in the government borrowing-to-GDP ratio will cause the CPI to decline by 0.3409. The negative coefficient may suggest a relatively strong crowding-out effect, causing consumption and investment spending to decline more than deficit-financed spending.…”
Section: Resultscontrasting
confidence: 73%
“…Wang et al (2014 used the SVAR approach to analyze the impact of different oil-related shocks on various agricultural commodity prices. SVAR approach has been widely used as well (Vo et al 2018;Nguyen and Vo 2019). The study found that the impact of oil-specific demand shocks on the many agricultural commodity prices was only significant after the food price crisis.…”
Section: Literature Reviewmentioning
confidence: 99%